Effects of Art Therapy on Autistic Children with Visual Impairment - Verma, Charu (International Multidisciplinary Research Journal, 2023)
The use of art in therapeutic form is very popular and its benefits are proven. Many therapists employ artistic methods to address the complications of autism for a long time but the increased prevalence of autism spectrum disorder with visual impairment is being witnessed these days. The present study aims to study the effects of art therapy intervention on the dual disability of autism and blindness. For this study two children having moderate autism with visual impairment were selected. Activities planned for them majorly focused on the stimulation of their tactile senses. The art therapy project for these students was divided into four stages: Pre-stage - the exploration of art material. In this stage, children were made familiar with different art materials. The second stage included tactile art-sand drawing, and the third and last stage activities were coins activity and paper weaving activity. It was designed to enhance motor skills and coordinated hand and body movement. There was resistance shown by both of them at the initial stage. However, the results after extensive sessions of their participation in activities indicated positive improvement in concentration. Their typical behavior of avoidance was also reduced. The results suggest that a tailored approach with the coordination of other experts and parents can help to overcome the complexity of their disorder.